Pericardial effusion complicating breast cancer. - Woll, P J (1987)
Thirty-five patients with metastatic breast cancer and pericardial effusions are described. They were treated with specific endocrine or chemotherapy. Twenty-two (63%) had presented in cardiac tamponade and were rapidly relieved by pericardiocentesis. Eighteen (82%) of these required no further local treatment, 2 obtained relief from a second aspiration and 2 needed additional treatment (intrapericardial bleomycin instillation and surgical pleuropericardial window). The median survival was 13.2 months. No patient relapsed again in the pericardium, suggesting that their prognosis was that of the underlying disease. Cardiac tamponade should be considered in any breathless patient with malignancy. In breast cancer, periocardiocentesis is lifesaving and systemic treatment can usefully prolong life.